2015
DOI: 10.1021/acs.langmuir.5b00063
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Fluorescence Behavior of 1-Pyrenesulfonate by Cointercalation with a Surfactant in a Layered Double Hydroxide

Abstract: Zn-Al layered double hydroxides (LDHs) containing solely 1-pyrenesulfonate (PS) or 1-heptanesulfonate (HS) anions, or a mixture of the two with HS/PS molar ratios ranging between ca. 7.5 and 82, were prepared by the direct synthesis method and characterized by powder X-ray diffraction, thermal and elemental analyses, scanning electron microscopy, and FT-IR, FT-Raman, and (13)C{(1)H} CP MAS NMR spectroscopies. Well-ordered intercalates were obtained with basal spacings of 18.8 Å for the LDH intercalated by PS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 63 publications
3
20
0
1
Order By: Relevance
“…Costa et al prepared Zn−Al layered double hydroxides (LDHs) containing solely 1pyrenesulfonate (PS) or 1-heptanesulfonate (HS) anions, or a mixture of the two molecules with HS/PS molar ratios ranging between 7.5 to 8.2, by a direct synthesis method. 195 The obtained solids were characterized by different experimental techniques including FT-IR, FT-Raman, and 13 C{ 1 H} CPMAS NMR spectroscopy.…”
Section: Intercalated Ldhsmentioning
confidence: 99%
“…Costa et al prepared Zn−Al layered double hydroxides (LDHs) containing solely 1pyrenesulfonate (PS) or 1-heptanesulfonate (HS) anions, or a mixture of the two molecules with HS/PS molar ratios ranging between 7.5 to 8.2, by a direct synthesis method. 195 The obtained solids were characterized by different experimental techniques including FT-IR, FT-Raman, and 13 C{ 1 H} CPMAS NMR spectroscopy.…”
Section: Intercalated Ldhsmentioning
confidence: 99%
“…The cointercalation of photofunctional molecules with surfactants has also been widely reported as an efficient way to tune and control the molecular packing mode within the LDH interlayer, which is of critical importance when designing efficient optoelectronic and photofunctional materials (vide supra). The surfactant may provide a homogenous nonpolar microenvironment by minimizing molecule aggregation and self‐quenching phenomena . Cointercalation can be carried out either by performing an anion exchange or through a direct synthesis route at constant pH or using a nucleation/crystallization separation method.…”
Section: New Trends and Strategies For Ldh And Hybrid Ldh Synthesismentioning
confidence: 99%
“…In both cases, an aqueous mixture of the two molecular guests in a suitable molar ratio is used. A broad range of active species has been immobilized using such a strategy, like α‐naphthalene acetate, (sulforhodamine B, 4‐(4‐anilinophenylazo)benzenesulfonate, fluorescein, coumarin‐3‐carboxylate, (1‐anilinonaphthalene‐8‐sulfonate, 8‐hydroxypyrene‐1,3,6‐trisulfonate, 2‐phenylbenzimidazole‐5‐sulfonate, 1‐pyrenesulfonate, zinc phtalocyanine . Wei and co‐workers demonstrated that size matching between the surfactant and the functional molecule favors sample homogeneity and fluorescence performances .…”
Section: New Trends and Strategies For Ldh And Hybrid Ldh Synthesismentioning
confidence: 99%
“…An outline of the basic photochemistry of pyrene is given in the Supporting information. For this work, the important features are: (a) pyrene monomer fluorescence shows a series of vibrational bands, the relative intensities of which vary with environment polarity (Kalayanasundaram & Thomas, 1977); and (b) the kinetics of pyrene excimer formation can be used to assess environment viscosity (Costa, Gomes, Pillinger, Goncalves, & Seixas de Melo, 2015;Glushko, Thaler, & Karp, 1981). Pyrene excimer formation has been widely studied in many different environments (Birks, Dyson, & Munro, 1963;Birks, Lumb, & Munro, 1964;Montalti, Credi, Prodi, & Gandolfi, 2006).…”
mentioning
confidence: 99%